Study of clinical profile and outcome of gall bladder perforations at a tertiary care centre from central India - Jain, Suraj; Kolla, Venkatesh; Datey, Sanjay; Vasistha, Rishikant (International Surgery Journal, 2016)
Background:Amongst the diseases of gall bladder calculous cholecystitis is the most common. Acute cholecystitis can worsen and result in various complications. Gall bladder perforation leading to generalised peritonitis is a lethal complication. Methods: In this retrospective observational study we have reviewed 550 cases of acute cholecystitis who were admitted to our institution in 8 years i.e. from 2008 to 2015. Perforations due to other causes (trauma, iatrogenic causes, and carcinoma) were excluded. Niemeier classification was used to identify the patients. Direct-abdominal X-ray series, abdominal ultrasound scanning (US), abdominal contrast-enhanced computerized tomography (CECT), routine blood cell count, and blood chemistry tests were performed. Results:Fourteen cases (2.5%) were found to have gall bladder perforations during the course of investigations and intraoperatively. Ten (71.42%) were females out of the total fourteen patients. Mean age was 65 years and presenting features on admission were nausea, vomiting, abdominal pain, fever and variable general condition. Aetiopathology of gall bladder perforation remains obscure till date. This clinical condition still remains a diagnostic as well as therapeutic challenge to surgeons. On detailed review of literature, we could not get few references, as the condition is uncommon. Conclusions:We have done this study to analyse the variable clinical presentation, correlation of non-invasive investigations and intraoperative findings and outcome in cases of gall bladder perforations so as to improve our further management of such cases.